Development Communication in Indonesia: Programmes, Methods, and Approaches - Harun, Rochajat (FIkom Unisba, 2003)
Development communication is an art and science that has evolved through various communication activities and programs conducted over the past twenty years especially in the field of agricultural communication. Experiences in Indonesia are providing certain insights into the issue of communication in the agricultural development that can be made effective. In Indonesia, there is a variety of communication resources being marshalled to help agriculture develop. Farmer groups and Contact-Farmers are the essential social institutions within the agricultural communication framework in Indonesia. Several methodologies or approaches related to this foundation which have been implemented are: Farmer’s Agricultural and Rural Training Center (FAR-TC); Integrated Pest Management (IPM); Income Generating Project for Marginal Farmers and Landless (IGP); Decentralized Agricultural and Forestry Extension Project (DAFEP); and The Training and Visit System (T&V).